Síntese e avaliação das atividades fungicida, fitotóxica e citotóxica de derivados do glicerol contendo núcleo 1, 2, 3-triazólico - Moreira, Luiza Carvalheira (2019)
Triazolic compounds are a class that has generated great interest in the scientific environment, since they have a wide range of biological activities and various industrial applications. This work aimed to synthesize a series of derivatives of the glycer